(untitled) (International journal of artificial intelligence, 2025)
The article explores one the most vital physiological processes in the human body - gas exchange in the lungs. It describes how oxygen and carbon dioxide are exchanged between the alveoli and blood through diffusion, ensuring that the body receives oxygen and removes waste gasses efficiently. The structure and function of the lungs, as well as the mechanisms of external and internal respiration, are analyzed in detail. The article also discusses how diseases such as bronchitis, pneumonia, asthma, chronic obstructive pulmonary disease (COPD), and pulmonary fibrosis affect the gas exchange process and reduce oxygen supply to body tissues. It emphasizes the importance of maintaining health lungs through proper hygiene, avoiding smoking, exercising regularly , and breathing clean air. This working highlight the physiological and medical significance of pulmonary gas exchange and serves as a useful source for students, educators, and healthcare professionals interested in biology, medicine, and respiratory health.